2015
DOI: 10.1063/1.4922639
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic nanospheres with a handle—Local electrochemical deposition of Au or Ag at the apex of optically inactive W- or C-tips

Abstract: Articles you may be interested inTemperature dependence of exciton-surface plasmon polariton coupling in Ag, Au, and Al films on InxGa1−xN/GaN quantum wells studied with time-resolved cathodoluminescence

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…180 Some common alternative methods for AFM−TERS tip fabrication include functionalizing AFM tips with single Au nanoparticles 180−183 and electrodeposition of Ag and Au. 178,184,185 The use of commercially available Au-coated AFM tips for TERS has also been reported. 161,186 Tuning-fork-based AFM (shear force microscopy, SFM) has also been extensively used as a TERS platform.…”
Section: Afm and Stm Tip Fabricationmentioning
confidence: 99%
See 1 more Smart Citation
“…180 Some common alternative methods for AFM−TERS tip fabrication include functionalizing AFM tips with single Au nanoparticles 180−183 and electrodeposition of Ag and Au. 178,184,185 The use of commercially available Au-coated AFM tips for TERS has also been reported. 161,186 Tuning-fork-based AFM (shear force microscopy, SFM) has also been extensively used as a TERS platform.…”
Section: Afm and Stm Tip Fabricationmentioning
confidence: 99%
“…In AFM–TERS, the most common fabrication method for producing tips is thermal evaporation of Ag or Au onto a commercial Si or SiN AFM probe. ,,, The deposition thickness for Ag varies widely in the literature, generally in the range of 20–70 nm. , However, Au AFM tips are used far less frequently in the AFM–TERS literature, with the optimal thickness reportedly in the range of 50–80 nm. , Aluminum tips have also been fabricated using thermal evaporation for deep-ultraviolet (UV) TERS studies . Some common alternative methods for AFM–TERS tip fabrication include functionalizing AFM tips with single Au nanoparticles and electrodeposition of Ag and Au. ,, The use of commercially available Au-coated AFM tips for TERS has also been reported. , Tuning-fork-based AFM (shear force microscopy, SFM) has also been extensively used as a TERS platform. In general, tip fabrication for SFM experiments is identical to those discussed above for STM experiments, with the resulting tip then attached to a tuning fork. ,, Batch fabrication methods have also been developed to increase tip reproducibility.…”
Section: Single-molecule and High-resolution Tersmentioning
confidence: 99%
“…In addition, Kim et al demonstrated in situ growth of a Ag-coated Au nanoparticle at the apex of an AFM tip . Finally, electrochemical deposition of plasmonic nanoparticles at the conductive apex of a nanoprobe enables reproducible tips whose optical properties can be tailored. , Such methods allow researchers to tailor physical properties of constructed tips, such as plasmon frequency, for particular applications.…”
Section: Tersmentioning
confidence: 99%
“…Ma et al reported a method for the local deposition of spherical Au or Ag onto optically inactive W- or C- tips, which is achieved by the local charging of the electrodes with short pulses and the local build up of the ion concentration. 32 By tuning the pulse duration, deposition time, and the gap distance between the tip and the electrode, the diameter of the deposited nanospheres was varied from tens of nanometers to one micrometer. Bakhti and co-workers reported a technique to grow single gold filaments based on a bias-assisted electro-reduction of gold ions directly at the AFM tip apex.…”
Section: Tersmentioning
confidence: 99%